2017
DOI: 10.1089/cyber.2016.0451
|View full text |Cite
|
Sign up to set email alerts
|

Delay Discounting of Video Game Players: Comparison of Time Duration Among Gamers

Abstract: Video game addiction or Internet game disorder, as proposed by the DSM-5 (Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition), has similar criterion characteristics to other impulse control disorders. There is limited research examining video game addiction within a behavioral economic framework using delay discounting. The current study evaluated delay-discounting patterns of money and video game play by usual weekly hours of video game play. A total of 104 participants were split into 1 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…A CFA was performed to assess the relationship between the four functions of the VGFA-R and the six factors of the IGD scales. Previous literature (e.g., Buono et al, 2016, Buono et al, 2017) has already established the functions of the VGFA-R, and Pontes and Griffiths (2014) have cited previous studies that have established the factors of the IGD scale. Holtzman and Vezzu (2011) suggested that once an initial model is established, it is important to perform CFA to confirm that the hypothesized model provides a good fit to the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A CFA was performed to assess the relationship between the four functions of the VGFA-R and the six factors of the IGD scales. Previous literature (e.g., Buono et al, 2016, Buono et al, 2017) has already established the functions of the VGFA-R, and Pontes and Griffiths (2014) have cited previous studies that have established the factors of the IGD scale. Holtzman and Vezzu (2011) suggested that once an initial model is established, it is important to perform CFA to confirm that the hypothesized model provides a good fit to the data.…”
Section: Methodsmentioning
confidence: 99%
“…The Video Game Functional Assessment-Revised (VGFA-R; Buono et al, 2016) was designed and is the only assessment to evaluate the reinforcing behavioral motivation of video game players by assessing the function of their video game play. More recently, Buono et al (2017) found individuals reporting “high” levels of play (e.g., 24 h of gaming per week and above) were largely motivated by the escape/avoidance or social attention functions. While effective at evaluating an individual’s motivation for gameplay, further work on the VGFA-R is required to determine if high levels of play meet the criteria of IGD as outlined in the DSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…IGD patients exhibit disadvantageous decision making (Pawlikowski and Brand 2011), and the relevant brain regions include regions involved in valuation (nucleus accumbens (NAcc) and ventromedial prefrontal cortex (vmPFC)), exploration (medial temporal lobe, precuneus, and dorsomedial prefrontal cortex), and executive control (orbitofrontal cortex (OFC), dlPFC and dACC) (Qi et al 2016b). In particular, in delay-discounting tasks, IGD patients are insensitive to long-term gains and losses and choose short-term gains (Buono et al 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies centered on IGD indicate that between 3.7 and 13.0% of the adult general population met criteria for problematic internet use ( 19 , 20 ), and that IGD is more prevalent in young samples ( 21 ). Correlates of IGD include high levels of risk-taking behaviors and impulsivity, higher delay discounting, high sensitivity to social rejection and high levels in interpersonal conflict, harm-avoidance and interpersonal conflict ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%